El control de inventario y su incidencia en la contabilidad de la distribuidora L&R de propiedad del Sr. Loayza Frías Willan Fernando de la ciudad de Machala - Armijos Cabrera, Marina Elizabeth (2015)
To develop research proceeded to split into five chapters, in which the problem is analyzed and evaluated the operations of the company to design a system of inventory control, the same are described widely below. Chapter I, titled The Problem. The subjects using the justification analysis, formulation of the central and complementary problem and formulating objectives, financial analysis is shown. Inside the Chapter II Theoretical, describes each of the subjects involved in research, such as accounting concept, concepts, historical review, inventory, definition, types of inventory, inventory control and definition. Similarly contextual framework involving the continent where the Distributor L & R of the City of Machala is summarized. Chapter III Methodology, highlights the universe and sample, data collection techniques, variables and indicators and the methodological procedures. Chapter IV deals with the technical aspects of the analysis and interpretation of results, in which the hypotheses, variables and indicators is discussed further study and results of the observation guide, interview and questionnaire surveys were done. In Chapter V, in which the conclusions and recommendations of the investigation are identified and that will lead to the development of a proposal to set accounting practice of the organization. Finally, in Chapter VI, background name given to the proposal, justification, objectives, description of the proposed action plan, management of the proposal, expected results, and implementation of strategies intended to, budget and schedule: PROPOSAL called important aspects are analyzed.